Digital Dilemma : Human Rights in the Era of Cyber Crimes - Bhouradia, Rupali; Tyagi, Richa (Trinity Law Review, 2024)
The rapid pace of digitalization is reshaping the landscape of human rights,  presenting both opportunities and challenges. While digital technologies have  facilitated unprecedented access to information, communication, and economic  opportunities, they have also introduced new risks to fundamental human rights.  From privacy infringements and online surveillance to the spread of disinformation  and cybercrimes, the digital era presents a complex ethical dilemma that requires  careful consideration. At its core, human rights remain paramount in navigating  this digital information. The present paper shall explore the potential of digital  technologies; it is imperative to prioritize human rights as the cornerstone of ethical  and responsible digitalization efforts, ensuring that technology serves humanity’s  collective well-being and advances the principle of equality, justice, and dignity for  all. It shall highlight the major challenges posed to human rights by cyber offenses  such as privacy violations, freedom of expression, access to information, threat to  critical infrastructure, etc. The secondary method is employed by the scholar for the  collection of data.4
Keywords: Human Rights; UNCHR; Cyber-crimes; Government of India; Digitalization; ICT